(untitled) (Eurasian Journal of History, Geography and Economics, 2024)
The study studied the impact of East Asian crisis that happened in the late 90’s to one of the countries in the region, Thailand and how another country, China managed to overcome that crisis. Nearly all Thai economic sectors were exposed to the East Asian crisis. Thailand’s GDP growth, inflation, budget, and trade accounts exposed its flaws as one of the fastest-growing countries of the 1980s. CML boosts investment and economic growth. CML’s key downsides include financial instability, volatility, and foreign investor dependency. Results can inform some policy suggestions. They are export promotion, business restructuring, and financial reforms. Fiscal and monetary policies like strong government expenditure, low interest rates, and lower taxes stimulate demand and growth